Anxieties of Migration and Integration in Turbulent Times - Jakobson, Mari-Liis; King, Russell; Moroşanu, Laura; Vetik, Raivo (IMISCOE Research Series, 2023)
How do migration and integration change when 'crisis becomes normalcy'? This open access book investigates this question in the present context of turbulent times when, instead of dealing with one crisis, migrants, governments and whole societies have to cope within a complex web of multiple unsettling events that create anxieties about migration. Emphasising a plurality of theoretical perspectives and methodological approaches, as well as a variety of geographical settings in Europe and beyond, the chapters bring new insights into migrations produced by global political events, national political shifts, economic downturns and the Covid-19 pandemic. Special attention is given to both migrants' experiences and policy outcomes. The result is an impressive rethinking of the concepts and terminology applied to migration and integration, of interest to both students and policy-makers.